Osseous Choristoma of the Tongue: A Review of Etiopathogenesis - Edoardo Gorini; Mauro Mullace; Luca Migliorini; Emilio Mevio (Case Reports in Otolaryngology)
Osseous choristoma is a normal bone tissue in an ectopic position. In the oral region lingual localization occurs more frequently and the mass is generally localized on the dorsum of the tongue. Definitive diagnosis is obtained only after histopathologic examination. The etiology remains already debatable. The treatment of choice is surgical excision. In this paper we present a case of tongue osseous choristoma and a review of the literature.